Semiochemical Exploitation of Host-Associated Cues by Seven Melittobia Parasitoid Species: Behavioral and Phylogenetic Implications - González, Jorge M.; Camino, Dakota; Simon, Sabrina; Cusumano, Antonino (Frontiers in Ecology and Evolution, 2018)
Chemical compounds (infochemicals or semiochemicals) play an important role both in intra-specific and inter-specific communication. For example, chemical cues appear to play a key role in the host selection process adopted by insect parasitoids. In recent years significant advances have been made in order to understand the chemical ecology of insect parasitoids. However, little information is available about the evolution of semiochemical use in the host location process of insect parasitoids. Here we investigated the strategy adopted by seven closely related parasitoid species in the genus Melittobia when foraging for four different suitable hosts. By using an integrated approach that combined olfactometer bioassays and phylogenetic investigations, we found that: 1) exploitation of host-derived semiochemicals is widespread in the Melittobia genus; 2) there is specificity of attraction towards the different host species tested; in particular, the early-branching species in the Melittobia genus are attracted to odors associated with leaf cutting bees (Megachile rotundata) whereas the most-diverged species are attracted to odors associated with solitary mud dauber wasps (Trypoxyilon politum). Regardless of the phylogenetic relationships, no Melittobia species exhibited attraction towards odors of factitious laboratory hosts (i.e. the flesh fly Sarcophaga bullata). Interestingly, five Melittobia species are also attracted by odors associated with honeybees hosts which indicate that these parasitoids could be potential pests of honeybees. Our study shed light on the host location within the Melittobia genus and represents a first attempt to understand semiochemical use in an evolutionary perspective in the context of parasitoids’ foraging behavior.